New soliton solutions of the fractional Regularized Long Wave Burger equation by means of conformable derivative - Korpinar, Zeliha; Tchier, F.; İnç, Mustafa; Ragoub, L.; Bayram, M. (Elsevier, 2019)
In this paper, the practice of the extended direct algebraic method (EDAM) is used to solve fractional Regularized Long Wave Burgers (RLW-Burgers) equation by means of the conformable derivative. Firstly, this fractional equation is changed into the ordinary differential equation by using the traveling wave transformation. Then new soliton solutions are obtained by using EDAM. This presented form is important in physics and engineering. The created soliton solutions play a major task for scientists about an agreement the physical event of this equation. The graphics of some solutions are drawn at fitting values of parameters. The obtained outcomes appear clarity, accuracy, and potentiality of the presented scheme.
Keywords: Solitons; RLW-Burgers equation; Conformable derivative; The extended direct algebraic method